2021
DOI: 10.1038/s41598-021-80996-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in hexaploid wheat identifies novel genomic regions associated with resistance to root lesion nematode (Pratylenchus thornei)

Abstract: Root lesion nematode (RLN; Pratylenchus thornei) causes extensive yield losses in wheat worldwide and thus pose serious threat to global food security. Reliance on fumigants (such as methyl bromide) and nematicides for crop protection has been discouraged due to environmental concerns. Hence, alternative environment friendly control measures like finding and deployment of resistance genes against Pratylenchus thornei are of significant importance. In the present study, genome-wide association study (GWAS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…Of these, the ones on chromosomes 4A and 5B were previously reported by Mulki et al [ 20 ]. In a similar study, Kumar et al [ 40 ] reported significant MTAs, on chromosomes 1B, 1D, 3B, and 6B, explaining 23% to 26% of the total phenotypic variation. The SNP marker S4B_539004405 was obtained in both repeats of CR under growth room conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Of these, the ones on chromosomes 4A and 5B were previously reported by Mulki et al [ 20 ]. In a similar study, Kumar et al [ 40 ] reported significant MTAs, on chromosomes 1B, 1D, 3B, and 6B, explaining 23% to 26% of the total phenotypic variation. The SNP marker S4B_539004405 was obtained in both repeats of CR under growth room conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Results from our procedure can provide insight into the evolutionary forces that act on the genomes of hexaploids and can also be used to detect genotyping errors in marker data. As the first step of molecular breeding in hexaploids, genome-wide association studies (GWAS) have been increasingly used as a routine approach for studying the genetic architecture of agriculturally important traits [ 32 34 ]. Our aHWE testing procedure provides valuable assistance for the quality control of markers and the evolutionary inference of any significant loci detected from GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…Many quantitative trait loci (QTLs) for P . thornei resistance have been reported in wheat (Kumar et al, 2021; Schmidt et al, 2005; Zwart et al, 2010). Several studies have reported QTLs associated with P .…”
Section: Introductionmentioning
confidence: 99%
“…RLNs are best managed through the incorporation into commercial crop cultivars of both genetic tolerance, that is the ability of a plant to minimize yield loss when grown in nematode-infested soil, and genetic resistance, that is the ability of a plant to inhibit nematode reproduction. Many quantitative trait loci (QTLs) for P. thornei resistance have been reported in wheat (Kumar et al, 2021;Schmidt et al, 2005;Zwart et al, 2010). Several studies have reported QTLs associated with P. neglectus resistance (Dababat et al, 2016;Mulki et al, 2013;Zwart et al, 2010); however, the QTLs often explained only a low proportion of genetic variation or they required validation in a genetically diverse panel or appropriate breeding populations before being suitable for use in marker-assisted selection (MAS).…”
mentioning
confidence: 99%